Status of Medical Library Resources and Services in Teaching Hospitals in Enugu State, Nigeria: implications for quality health care services. - Okeke, Oluch C.; S.G.N, Ezu; Eze, Jacintha U.; G.E., Asogwa (International Journal of Knowledge Content Development & Technology, 2017)
Considering the need for quality health information and resultant health care services in any society, this study was carried out to look into the status of library and information resources and services provided by medical libraries in Enugu State, Nigeria. The main objective of the study was to find out the information resources and services available for medical library users towards quality health care provision. Five (5) medical libraries of major teaching hospitals were used for the study with 980 registered users as the study population from where 245 users were sampled. Observation checklist was used to collect data on resources while questionnaire was used to collect data from the respondents on the services provided. The Medical Library Association Standard guided the analysis of data from observation while frequency counts and mean scores were used to analyze data from the questionnaire. Major findings showed that even though some of the required resources and services are available and provided the medical libraries, most of the required resources and services are not adequately provided by these libraries. URL: http://ijkcdt.net/xml/10970/10970.pdf